Chemical Recycling of PET Wastes with Different Catalysts. (29th October 2015) - Khoonkari, Mohammad; Haghighi, Amir Hossein; Sefidbakht, Yahya; Shekoohi, Khadijeh; Ghaderian, Abolfazl
Abstract : Chemical recycling of polyethylene terephthalate, known as PET, has been the subject of increased interest as a valuable feedstock for different chemical processes. In this work, glycolysis of PET waste granules was carried out using excess ethylene glycol in the presence of different simple chemicals acting as catalysts, which are, namely, categorized in ionic liquids, metal salts, hydrotalcites, and enzymes. From every category, some materials as a sample were used, and the one which is going to bring the best result is noted. The effect of some parameters such as temperature, pressure, amount of sample, material ratio, and stirring rate was investigated. As a result we compared the best of each category with the others and final result is shown.